2014
DOI: 10.1016/j.electacta.2013.08.133
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion mechanisms in aqueous solutions containing dissolved H2S. Part 2: Model of the cathodic reactions on a 316L stainless steel rotating disc electrode

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Corrosion mechanisms in aqueous solutions containing dissolved H 2 S. Part 2: Model of the cathodic reactions on a 316L stainless steel rotating disc electrode. AbstractIn H 2 S containing solutions, the reduction of protons with a buffer effect contributing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 18 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Considering that the slope of the trendline in this graph is nearly unity (1.02), the increase of the limiting current resulting from the presence of acetic acid was in linear correlation with the concentration of undissociated acetic acid (R 2 = 0.996), regardless of the bulk pH. Furthermore, the intercept of the trendline (3.98) was found to agree well with the theoretically obtained value of 4.01 from Levich equation (Equation [6]) (diffusion coefficient and water kinematic viscosity from Nordsveen, et al 5 ). This agreement indicated that the measured limiting currents are under pure mass transfer control; thus, the surface concentration of undissociated acetic acid was negligibly small.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Considering that the slope of the trendline in this graph is nearly unity (1.02), the increase of the limiting current resulting from the presence of acetic acid was in linear correlation with the concentration of undissociated acetic acid (R 2 = 0.996), regardless of the bulk pH. Furthermore, the intercept of the trendline (3.98) was found to agree well with the theoretically obtained value of 4.01 from Levich equation (Equation [6]) (diffusion coefficient and water kinematic viscosity from Nordsveen, et al 5 ). This agreement indicated that the measured limiting currents are under pure mass transfer control; thus, the surface concentration of undissociated acetic acid was negligibly small.…”
Section: Resultssupporting
confidence: 84%
“…Hydrogen sulfide is an example of one such weak acid, where a double wave similar to what is schematically shown in Figure 1(a) was observed. 3,[6][7]41 This double wave was shown to be associated with the mass transfer limiting currents of hydrogen ion reduction and hydrogen sulfide direct reduction. 3 While the presence of the double wave is a strong indication of the weak acid direct reduction, its absence is not conclusive evidence for dismissing this reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution XPS spectra of N 1s of mild steel obtained after immersion in H 2 S and CO 2 saturated brine solution with (a) 50 mg L À1 of 12-3OH-12, (b) 100 mg L À1 of QB, (c) 100 mg L À1 of QB + 10 mg L À1 of 12-3OH-12, (d) 100 mg L À1 of QB + 30 mg L À1 of 12-3OH-12, (e) 100 mg L À1 of QB + 50 mg L À1 of 12-3OH-12 and (f) 100 mg L À1 of QB + 70 mg L À1 of 12-3OH-12 at 60°C. quaternary ammonium ions, ionized from QB and 12-3OH-12 molecules, can be adsorbed on the layer of adsorbed anions through electrostatic interaction [39,56,57]. Subsequently, chemisorption may take place.…”
Section: Synergism Mechanism Of Qb and 12-3oh-12mentioning
confidence: 99%
“…The second question is related to the mass transfer rate for the reaction involving direct reduction of H 2 S. In Zheng et al's study 9 on carbon steel corrosion, the measured values of mass transfer limiting current density agreed very well with the calculation of mass transfer rates by Eisenberg correlation using an RCE. However, in Kittel et al 8 and Tribollet et al's research 15 , the measured limiting current density of H 2 S reduction was lower than the calculation by the Levich law. One of their suspicions was related to the use of different materials: carbon steel vs. stainless steel.…”
Section: Investigation Of Electrochemical Kinetics Of H 2 S Reductionmentioning
confidence: 74%